HIT NOISE REDUCTION IN SOME X-RAY IMAGES - Al-Zuky, Ali Abid D; Kzar, Ahmed Asal (Al-Nahrain Journal of Science, 2018)
The imaging system we have investigating suffer from the appearance of scattered bright points. A usual solution to reduce this noise can be achieved by an increase in exposure but it is very difficult to prevent the hits. In present study, we have investigating algorithms to reduce noise with out an increase in exposure by adopting four digital filters for noise reduction and comparing between efficiency of each filter to determine an efficient method. The resulting images and fidelity criteria showed that the median filter smoothes hit noise while maintaining edge information, but the mean filter image is a blurred version of the noisy image.